Mycobacterium tuberculosis: An Adaptable Pathogen Associated With Multiple Human Diseases - Chai, Qiyao; Zhang, Yong; Liu, Cui Hua (Frontiers in Cellular and Infection Microbiology, 2018)
Mycobacterium tuberculosis, the etiological agent of tuberculosis (TB), is an extremely successful pathogen that adapts to survive within the host. During the latency phase of infection, M. tuberculosis employs a range of effector proteins to be cloud the host immune system and shapes its lifestyle to reside in granulomas, sophisticated, and organized structures of immune cells that are established by the host in response to persistent infection. While normally being restrained in immunocompetent hosts, M. tuberculosis within granulomas can cause the recrudescence of TB when host immunity is compromised. Aside from causing TB, accumulating evidence suggests that M. tuberculosis is also associated with multiple other human diseases, such as pulmonary complications, autoimmune diseases, and metabolic syndromes. Furthermore, it has been recently appreciated that M. tuberculosis infection can also reciprocally interact with the human microbiome, which has a strong link to immune balance and health. In this review, we highlight the adaptive survival of M. tuberculosis within the host and provide an overview for regulatory mechanisms underlying interactions between M. tuberculosis infection and multiple important human diseases. A better understanding of how M. tuberculosis regulates the host immune system to cause TB and reciprocally regulates other human diseases is critical for developing rational treatments to better control TB and help alleviate its associated comorbidities.